Scaling Multilingual XGLM for Educational Dialogue Act Classification in Indonesian and English - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 8 peer-reviewed papers addressing the following research question: How does the multilingual capability of XGLM-564M scale with model size (e.g., 564M vs. 1.7B) for educational dialogue act classification, measured by accuracy differences between Indonesian and. 17 claims were extracted from source literature; 4 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.5/10. This report is a
Machine-generated literature synthesis.